2010
DOI: 10.21649/akemu.v15i1.24
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Nutritional Status of Adolescent College Girls at Rawalpindi

Abstract: Objectives: To assess the nutritional status of adolescent college girls by assessing the dietary intake in terms of carbohydrates, proteins, Estimating the hemoglobin levels in the study group and studying the clinical signs of malnutrition with special emphasis to vitamin A, iron and iodine deficiency. Design of Study:A cross-sectional study.Settings: Two Post-Graduate women colleges of Rawalpindi. Materials and Methods:Nutritional status of 508 adolescent girls was assessed with a questionnaire, clinical ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 5 publications
5
15
2
Order By: Relevance
“…Other studies (Fikru, 2014) conducted in South East Oromiya, Ethiopia on randomly selected adolescents reported that mean pulse consumption was significantly improved from 5.29 (4.3) at baseline to 12.44 (4.8) after six months of pulse nutrition education in the intervention group. Other studies such as Shahidet.al (Shahid, et al, 2009) also reported the same results.…”
Section: Discussionsupporting
confidence: 74%
“…Other studies (Fikru, 2014) conducted in South East Oromiya, Ethiopia on randomly selected adolescents reported that mean pulse consumption was significantly improved from 5.29 (4.3) at baseline to 12.44 (4.8) after six months of pulse nutrition education in the intervention group. Other studies such as Shahidet.al (Shahid, et al, 2009) also reported the same results.…”
Section: Discussionsupporting
confidence: 74%
“…Hence, adolescents were more affected by stunting despite improving conditions over time now days. The prevalence of thinness 19.5%, was goes in line with a study conducted in Adwa, a study conducted in Wukro, northern Ethiopia, a study conducted in Babile district, eastern Ethiopia and a study conducted in Rawalpindi, India which were 21.4%, 21.6%, 21.6% and 20% [2,19,22,35]. However, the prevalence in the current study was much lower than studies conducted in eastern Tigray which was 33.7% [4], a study conducted in four zones (central, eastern, north-western and southern zones) of Tigray, northern Ethiopia which was 58.3% [20] and studies conducted in different areas of India which were 25.7%, 28.2%, 43.5% and 48.0% respectively [13,23,32,36,37].…”
Section: Discussionsupporting
confidence: 81%
“…A.S.Indupallli 6 observed that 27.6% of adolescent girls were suffering from chronic energy deficiency and 72.4% were nutritionally normal, while no one was overweight. Shahid et al 7 conducted a study in Pakistan among adolescent girls and results revealed that 20% of girls had BMI <18.5 and 3% were obese. The high prevalence of malnutrition in our study might be because most of the girls were from the lower socio economic status.…”
Section: Discussionmentioning
confidence: 99%